Analysis of risk factors of stillbirth: a hospital based study in a tertiary care centre - Shyam, Paresh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Stillbirth is an indicator of maternal health and maternal health care services. Developing countries have high stillbirth rate. Documentation and evaluation of the risk factors for stillbirth is required for management of the risk factors and to devise plan in maternal health sector. Methods: It was a hospital based retrospective study carried out in a tertiary care hospital. Inclusion criteria were a case of fetal death with gestational age ≥20 weeks or fetal weight ≥ 500gm. Results: Total birth during the study period was 5132 and stillbirth 282. Stillbirth rate was 5.4% (54/1000). Majority of patients were primigravida (52.59%). Risk factors were detected in 164 (60.74%). Incidence of some of the risk factors were hypertensive disorder of pregnancy 46 (17.03%), antepartum haemorrhage 33 (12.22%), IUGR 11 (4.07%), Malpresentation 15 (5.55%) and fetal anomalies 4 (1.48%). Stillbirth without risk factors was 106 (39.25%). Conclusion: Majority of the risk factors found in the present study were preventable. Stillbirth rate can be reduced by proper management of these risk factors during antenatal care and intrapartum care.